PENGARUH PELAKSANAAN PRAKTEK KERJA INDUSTRI ( PRAKERIN ) TERHADAP HASIL UJI KOMPETENSI KEAHLIAN SISWA KELAS XII TN SMK NEGERI 2 NGANJUK - DWI JAYANTI, RETNO (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
Competition in getting jobs by SMK graduateds is very competitive. This need to be supported by competent graduated competencies appropriated to their expertise. So the students are required to implement of industrial work practice. This program is expected to help students in implementing competency test that will get better. This study aims to identify and analyze the effect implementation of industrial practice on student competency test resulst of class XII TN SMK Negeri 2 Nganjuk. The population and sample is student of class XII TN was 63 students. Based on the data analyze with simple regression analysis, R Square resulting value of 0,840 means that implementation of industrial practice influenced competency test results of class XII TN SMK Negeri 2 Nganjuk by 84%, while the remaining 16% are caused by the other factors. The results showed that there was effect of the variable implementation of industrial practice to competency test results of class XII TN SMK Negeri 2 Nganjuk. Keywords : Industrial Work Practice, Competency Tests.